Two-fold addition reaction of silylene to C60: structural and electronic properties of a bis-adduct - Kako, Masahiro; Kai, Masato; Yasui, Masanori; Yamada, Michio; Maeda, Yutaka; Akasaka, Takeshi (Beilstein Journal of Organic Chemistry, 2024)
The addition reaction of C60 with silylene 1, a silicon analog of carbene, yielded the corresponding bis-adduct 3. The structure of 3 was determined by single-crystal X-ray structure analysis, representing the first example of a crystal structure of a silirane (silacyclopropane) derivative of fullerenes. Electrochemical measurements confirmed that the redox potentials of 3 are shifted cathodically compared to those of the parent mono-adduct 2. Density functional theory (DFT) calculations provided the basis for the electronic properties of compound 3.
Keywords: bis-adduct; C60; fullerene; silirane; silylene